Comparative Diagnostic Accuracy of CT and Ultrasonography for Bowel Obstruction: A Systematic Review and Meta-Analysis - Moch Nurul Jadid; Dono Marsetio Wibiseno (Open Access Indonesian Journal of Medical Reviews, 2025)
The prompt and accurate diagnosis of bowel obstruction is a critical challenge. This systematic review and meta-analysis aimed to determine and compare the pooled diagnostic accuracy of computed tomography (CT) and ultrasonography (USG) for detecting bowel obstruction in adult patients. Following PRISMA-DTA guidelines, we systematically searched PubMed, ScienceDirect, and SagePub for primary diagnostic accuracy studies published between 2014 and 2024 that evaluated CT and/or USG against a reference standard (surgical findings or clinical follow-up). Two reviewers independently screened studies, extracted data, and assessed bias using the QUADAS-2 tool. Bivariate random-effects models were used to calculate pooled sensitivity and specificity. Our search yielded 15 studies comprising 2,876 patients. For the diagnosis of bowel obstruction, CT had a pooled sensitivity of 95.2% (95% CI: 92.8%–96.9%) and a pooled specificity of 96.1% (95% CI: 93.5%–97.7%). For USG, the pooled sensitivity was 91.5% (95% CI: 88.4%–93.8%), and the pooled specificity was 94.3% (95% CI: 91.2%–96.4%). The area under the summary receiver operating characteristic curve confirmed superior overall diagnostic performance for CT (0.98) compared to USG (0.95). In conclusion, CT demonstrates a slightly higher diagnostic accuracy than USG for bowel obstruction in adults. It should be considered the preferred modality for definitive evaluation, particularly for identifying etiology and complications. However, USG remains an excellent and highly accurate alternative, especially as a first-line, point-of-care tool in emergency settings, in pregnant patients, or where CT is contraindicated. The choice of modality should be guided by the specific clinical context.